Histochcmical studies on the cell types of the anterior lobe of rat hypophysis - Şadiye Ergüldürenler (Eurasian Journal of Veterinary Sciences)
The aim of this study was to investigate the histologic charastenctics of anterior pituitary cell types in the immature and mature males and also in immature, mature, pregnant and lactating lemale rats wilh the light microscope. As a material. 30 pituitary glands provided (rom Wistar albino rats were used (20 females and 10 males). Acidophilic cells were found to distribute throughout the pars distalis in all groups. These cells were round or ovoid in shape, and their nuclei were also round and localized cccenlrically and Ihe cells in contact with sinusoids, Their numbers were more greater at both lactational and pregnancy than these of Ihe other stages. AII ho ugh the lipotropic cells distributed throughout the pars distalis, Ihese cells were observed more diffuse in the centrial and lateral areas of pars disialis, These cells were round, o void, stellar and vanous in shape, and their nuclei were large and round in shape. Their numbers were tho greatest in mature female and they were much more in female than mate. The round-ovoid shaped gonadotrophs cells were observed throughout the pars distalis. Their nuclei were round in shape. These cells were found at maximum numbers, depending on the sexual period in the mature lemale.